2014
DOI: 10.1136/bjophthalmol-2014-305333
|View full text |Cite
|
Sign up to set email alerts
|

Changes in subfoveal choroidal thickness associated with uveitis activity in patients with Behçet's disease

Abstract: This study indicates that measurement of subfoveal choroidal thickness by EDI-OCT is useful for evaluating the activity of uveitis and the therapeutic efficacy in patients with BD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
81
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(90 citation statements)
references
References 22 publications
9
81
0
Order By: Relevance
“…Recently, a new method of SD-OCT, termed enhanced depth imaging (EDI), has been shown to be capable of visualizing the full thickness of the choroid (8) . Changes in choroidal thickness have previously been reported in a number of autoimmune and systemic inflammatory disorders (9)(10)(11)(12)(13) . To the best of our knowledge, studies using EDI-OCT to evaluate choroidal segment involvement in patients with IBD have yet to be reported.…”
Section: Introductionmentioning
confidence: 94%
“…Recently, a new method of SD-OCT, termed enhanced depth imaging (EDI), has been shown to be capable of visualizing the full thickness of the choroid (8) . Changes in choroidal thickness have previously been reported in a number of autoimmune and systemic inflammatory disorders (9)(10)(11)(12)(13) . To the best of our knowledge, studies using EDI-OCT to evaluate choroidal segment involvement in patients with IBD have yet to be reported.…”
Section: Introductionmentioning
confidence: 94%
“…Ishikawa et al and Kim et al reported that subfoveal choroidal thickness was significantly higher during an acute attack of Behçet's uveitis than in remission. Their choroid was found thicker than that of healthy control subjects not only during an attack of Behçet's uveitis but also during remission of the disease [36,37].…”
Section: Complementary Imaging Modalities and Laboratory Testsmentioning
confidence: 72%
“…Detailed visualisation of the choroid in vivo is now possible thanks to enhanced depth imaging (EDI) optical coherence tomography (OCT) (10). Various studies that have used OCT to evaluate CT in several systemic autoimmune and infl ammatory disorders are available (11)(12)(13)(14). The aim of our study was to evaluate the choroidal thickness (CT) in patients with rheumatoid arthritis (RA) and detectthe relation with disease activity and joint damage in patients with rheumatoid arthritis, additionally compare it with healty controls.…”
Section: Introductionmentioning
confidence: 99%